The presence of elafin, SLPI, IL1-RA and STNFα RI in head and neck squamous cell carcinomas and their relation to the degree of tumour differentiation. Issue 1 (2002) - Westin, U.; Nyström, M.; Ljungcrantz, I.; Eriksson, B.; Ohlsson, K.
Abstract : Biopsy samples of head and neck carcinomas were investigated with regard to elafin, secretory leukocyte protease inhibitor (SLPI), interleukin 1-receptor antagonist [(IL)1-RA] and soluble tumour necrosis factor α receptor antagonist (STNFα RI). SLPI and elafin are serine protease inhibitors produced in the serous cells of the upper respiratory airways and in the keratinocytes, respectively. We have now found the presence of elafin and SLPI in squamous cell carcinomas of the upper respiratory tract (tonsillar, hypopharyngeal, tongue, mouth floor, gingival and laryngeal cancer). Significantly higher amounts of SLPI and elafin are present in well-differentiated and moderately differentiated tumours than in poorly differentiated tumours (p < 0.0001 andp < 0.0015 ). Tumour necrosis factor-α and IL-1β have been shown to stimulate the production of SLPI and elafin. Since these cytokines can both be difficult to detect, we chose to study their inhibitors, STNF α RI and IL1-RA, instead. IL1-RA was expressed in highly differentiated tumours as well as in poorly differentiated ones. No significant difference was seen between the groups. STNF α RI was only found in very small amounts, sparsely distributed in the tumours, and was not related to the degree of differentiation.